Effects of Inflation, Sharia Bank Financing, and Conventional Bank Credit on Gross Regional Domestic Product - Kartasiah, Kartasiah; Maulida, Sri (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2024)
This research aims to know the impact of inflation, conventional BPR loans, and sharia BPR financing on the regional Gross Domestic Product (GDP) of Southern Kalimantan Province. This research uses secondary data (time series) for 2017-2021, collected from the official website of the Southern Kalimantan Statistical Centre and the Financial Services Authority. The study used a double linear regression analysis method using the Eviews-12 application. This study concluded that in part inflation of the region has no impact on the regional GDP, in part conventional BPR loans and sharia BPR financing have a significant positive effect on the regional GDP, and simultaneously the variable inflation, conventional BPR loans and sharia BPR financing has an impact on regional GDP of the Province of Southern Kalimantan.